Solve ut+3ux=0, where -infinity < x < infinity, t>0, and u(x,0)=f(x).
Fourier Transform where (U=fourier transform of u)
The Attempt at a Solution
I've used Fourier transform to get that Ut-3iwU=0 and that U=F(w)e3iwt. However, I'm completely stuck trying to find the inverse Fourier transform of e3iwt in order to use the convolution theorem; I suspect that it's a dirac delta function of t-3t, but the table that I'm using doesn't have this general form and contains a 1/2pi constant at the front for the function to be transformed.